SOME PRELIMINARY RESULTS ON THE DISTRIBUTION OF AFTERSHOCK SEQUENCES IN JAPAN-KURIL ISLANDS AND KAMCHATKA - Olasoglou, E.M.; Tsapanos, T.M.; Papadimitriou, E.E.; Drakatos, G.N. (Bulletin of the Geological Society of Greece, 2016)
study on the aftershock sequences distributed along the subductions in Japan and Kuril islands, as well as in Kamchatka is undertaken. Aftershock sequences, having a main shock magnitude Mw >7.0, during the time period 1973-2013 are taken into account. The data used (mainshocks, aftershocks and foreshocks if there are any) are restricted in shallow focal depths. A large earthquake in Japan Trench (11 March 2011 / Mw=9.0) occurred and for this reason the investigated area is of particular interest. Our study is concentrated on the spatial distribution of some parameters [Mc, a, b (Gutenberg-Richter distribution) and p, c, k (Omori’s law)] closely associated with the seismic sequences statistics.